Case Report: Failed response to anti-PD-1 immunotherapy in a colon cancer patient with high microsatellite instability - Li, Rong; Lin, Yan-Ping; Shen, Xin; Guo, Jiang-Yan; Zhang, Ya; Tang, Jia-Dai; Xie, Lin; Hu, Feng-Di (Frontiers in Oncology, 2025)
BackgroundAlthough immune checkpoint inhibitors (ICIs) have achieved remarkable progress in the treatment of deficient mismatch repair (dMMR)/high microsatellite instability (MSI-H) colorectal cancer (CRC), nearly 50% of dMMR/MSI-H CRC patients exhibit primary resistance to immunotherapy.Case summaryAn 84-year-old male patient was diagnosed with poorly differentiated adenocarcinoma of the right hemicolon (pT3N2M1c, stage IVc, dMMR). The patient underwent palliative surgery of the right hemicolon and subsequently received 3 cycles of bevacizumab in combination with capecitabine. Genetic testing revealed MSI-H/TMB-H/HLA heterozygosity. When the patient came to our center for treatment, we adjusted the treatment regimen to tislelizumab immunotherapy for 4 cycles. After immunotherapy, a CT review revealed disease progression. Moreover, the patient’s physical strength deteriorated dramatically, with an Eastern Cooperative Oncology Group (ECOG) score of 3. The patient subsequently received best supportive care. The patient’s overall survival (OS) was 9 months.ConclusionThe continued success of immunotherapy in dMMR/MSI-H CRC faces challenges related to immune resistance. Further studies are needed to uncover the mechanisms, targets, and biomarkers involved.